THE EFFECT OF ENTREPRENEURSHIP KNOWLEDGE, SOCIAL MEDIA AND SELF EFFICACY ON STUDENT'S INTEREST IN BECOME ENTREPRENEURS - Razali, Ramadhan; Nasution, Muhammad Syafril; Yulia, Sri (Corolla International Conference, 2022)
Entrepreneurship is considered an important mechanism that results in inclusive and sustainable development through employment, innovation, competitiveness and prosperity. This study aims to determine the effect of entrepreneurial knowledge, social media and self-efficacy partially and simultaneously on students' interest in becoming entrepreneurs using quantitative methods. Sampling using purposive sampling technique. Data collection was carried out by distributing online questionnaires as many as 141 students as respondents. Data processing with multiple linear regression testing with the help of SPSS 26 software. Based on the results of the study, it can be concluded that: 1) Entrepreneurship Knowledge variable does not affect the interest of FEBI IAIN Lhokseumawe students to become entrepreneurs. 2) Social Media variables have a positive and significant effect on the interest of FEBI IAIN Lhokseumawe students to become entrepreneurs. 3) The Self Efficacy variable has a positive and significant effect on the interest of FEBI IAIN Lhokseumawe students to become entrepreneurs. 4) Knowledge of Entrepreneurship, Social Media and Self Efficacy variables simultaneously have a positive and significant effect on the interest of FEBI IAIN Lhokseumawe students to become entrepreneurs.